Tourism management and sustainable development - Karanovic, Goran; Polychronidou, Persefoni; Karasavvoglou, Anastasios; Ribaric, Helga Maskarin (Switzerland Springer Nature, 2021)
This book investigates the various ties between tourism development and sustainability, revealing forces of change and current trends in tourism management performance in countries of Central and Southeast Europe. The contributions explore how the tourism industry is responding to numerous related challenges while managing risks with the aim of enhancing tourism management performance. In addition, it offers insights into the interconnections between tourism and other industries.